Energetic and biomechanical contributions for longitudinal performance in master swimmers - Marinho, D.A. (2020)
The current study aimed to verify the changes in performance, physiological and biomechanical variables throughout a season in master swimmers. Methods: Twenty-three master swimmers (34.9 ± 7.4 years) were assessed three times during a season (December: M1, March: M2, June: M3), in indoor 25 m swimming pools. An incremental 5 × 200 m test was used to evaluate the speed at 4 mmol·L−1 of blood lactate concentration (sLT), maximal oxygen uptake (VO2max), peak blood lactate ([La-]peak) after the test, stroke frequency (SF), stroke length (SL), stroke index (SI) and propelling efficiency (ηp). The performance was assessed in the 200 m front crawl during competition. Results: Swimming performance improved between M1, M2 (2%, p = 0.03), and M3 (4%, p < 0.001). Both sLT and VO2max increased throughout the season (4% and 18%, p < 0.001, respectively) but not [La-]peak. While SF decreased 5%, SL, SI and ηp increased 5%, 7%, and 6% (p < 0.001) from M1 to M3. Conclusions: Master swimmers improved significantly in their 200 m front crawl performance over a season, with decreased SF, and increased SL, ηp and SI. Despite the improvement in energetic variables, the change in performance seemed to be more dependent on technical than energetic factors